2017
DOI: 10.1080/19475705.2016.1278404
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the spatial variability of wildfire susceptibility in Honduras using remote sensing and geographical information systems

Abstract: Forests in Honduras are endangered as a result of the relentless occurrence of wildfires during the dry season, and their frequency and area burned have been gradually increasing, a pattern attributable to the numerous ignition sources. For this reason, there is a substantial need to identify the major drivers of wildfires and map the regions where they are most likely to occur. In this study, we integrated the wildfire occurrences throughout the 2010-2015 period with a series of variables using the random for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Based on the outputs of decision tree assessments, the majority vote converges on a single decision tree for the final classification [44]. In order to overcome the uncertainty problem, a single decision tree can be used, and this will result in higher prediction accuracy [45]. The crucial step in the RF classification is to derive high variance from different decision trees.…”
Section: Random Forest (Rf)mentioning
confidence: 99%
“…Based on the outputs of decision tree assessments, the majority vote converges on a single decision tree for the final classification [44]. In order to overcome the uncertainty problem, a single decision tree can be used, and this will result in higher prediction accuracy [45]. The crucial step in the RF classification is to derive high variance from different decision trees.…”
Section: Random Forest (Rf)mentioning
confidence: 99%
“…The (AUROC) curve technique was selected for this comparison. It is commonly used to characterize the quality of the resulting susceptibility-prediction maps, particularly in the geosciences [107,108]. The plotted curves display the trade-offs between the false positive rate (FPR) and the true positive rate (TPR), on the X and Y axis, respectively.…”
Section: Accuracy Assessmentsmentioning
confidence: 99%
“…Research projects and works on wildfire hazard and risk mapping are numerous and diverse; complete compilations on such studies can be found in [18][19][20]. Regarding the scale, these studies include long-term, short-term and real-time approaches, from the time scale point of view, while global, regional, and local scales may be used as spatial scales.…”
Section: Introductionmentioning
confidence: 99%